2011
DOI: 10.1128/iai.05591-11
|View full text |Cite
|
Sign up to set email alerts
|

Candida albicans Cell Wall Glycosylation May Be Indirectly Required for Activation of Epithelial Cell Proinflammatory Responses

Abstract: Oral epithelial cells discriminate between the yeast and hyphal forms of Candida albicans via the mitogenactivated protein kinase (MAPK) signaling pathway. This occurs through phosphorylation of the MAPK phosphatase MKP1 and activation of the c-Fos transcription factor by the hyphal form. Given that fungal cell wall polysaccharides are critical in host recognition and immune activation in myeloid cells, we sought to determine whether ␤-glucan and N-or O-glycosylation was important in activating the MAPK/MKP1/c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
30
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 43 publications
4
30
0
1
Order By: Relevance
“…This category included genes responsible for N-linked glycosylation, hexosylation, and mannosylation (e.g., MNT2, MNT3, and PMT5), all of which were downregulated in cells colonizing the ileum (see Table S5 in the supplemental material). Because a decreased inflammatory response in response to C. albicans mutants defective in glycosylation was observed (75), decreased or altered patterns of glycosylation may allow colonizing cells to avoid the immune response. In addition, cells with deficiencies in mannosylation are more resistant to phagocytosis by neutrophils (76).…”
Section: Resultsmentioning
confidence: 99%
“…This category included genes responsible for N-linked glycosylation, hexosylation, and mannosylation (e.g., MNT2, MNT3, and PMT5), all of which were downregulated in cells colonizing the ileum (see Table S5 in the supplemental material). Because a decreased inflammatory response in response to C. albicans mutants defective in glycosylation was observed (75), decreased or altered patterns of glycosylation may allow colonizing cells to avoid the immune response. In addition, cells with deficiencies in mannosylation are more resistant to phagocytosis by neutrophils (76).…”
Section: Resultsmentioning
confidence: 99%
“…The mannans of yeast and hyphae differ physically and chemically (e.g. [23 ]) and this may contribute to the differential immune reactivity of these two morphological forms together with morphology associated proteins [47,48 ]. For example, surface-associated pH-regulated antigen 1 protein (Pra1), a predominantly hypha-associated protein, plays a pivotal role in the recognition of C. albicans by human neutrophils and enhances neutrophil antimicrobial responses.…”
Section: Recognition During Morphogenesis Commensalism and Pathogenesismentioning
confidence: 99%
“…Subsequently, in the same model, we showed that activation of this pro-inflammatory response by C. albicans results in recruitment of polymorphonuclear (PMN) cells and protection against fungal invasion and infection in a toll-like receptor (TLR)4-dependent manner [2]. Others have also confirmed that C. albicans stimulates cytokine production in mucosal monolayer cell lines and primary mucosal cells [10], [11], [12], [13], [14], [15], [16]. However, despite recent progress, the nature of C. albicans surface moieties responsible for epithelial cell immune activation is undefined.…”
Section: Introductionmentioning
confidence: 94%